Program Dakwah Pemberdayaan Keluarga Dhuafa melalui Kuliah Kemuhammadiyahan Universitas Muhammadiyah Jakarta - Habibi, Mulkan; Purwanto, Hari Eko; Fakhrurazi, Fakhrurazi; Mansah, Adi; Cholinny, Mycroft Diaz (Universitas Pahlawan Tuanku Tambusai, 2025)
The empowerment program through the Kemuhammadiyahan course is an implementation of Al-Ma’un theology, which teaches compassion for others through acts of social charity. This movement is realized in the form of empowering underprivileged families (keluarga dhuafa). Student groups formed as part of this course will carry out the empowerment process through an economic approach by involving various stakeholders to ensure the activities run effectively and systematically. The empowerment methods include mentoring and support based on a productive assistance approach.As a result of this empowerment, students gain a deep understanding of the social realities around them, along with the ability to design solutions rooted in Islamic and humanitarian values. Meanwhile, beneficiary families gain new hope of breaking the cycle of poverty through measurable and sustainable efforts. Overall, this program not only provides direct benefits to underprivileged families but also instills the spirit of Al-Ma’un within students, shaping them into compassionate future Muslim intellectuals who are capable of becoming agents of change in society.